Antimicrobial and anticancer activities of organoiron melamine dendrimers capped with piperazine moieties. (September 2016) - Abd-El-Aziz, Alaa S.; Abdelghani, Amani A.; El-Sadany, Samir K.; Overy, David P.; Kerr, Russell G.
Graphical abstract: Three generations of bioactive melamine dendrimers containing organoiron moieties were successfully synthesized. Several end groups such as chloro-, hydroxyl-, or piperazine were used to efficiently functionalize the designed dendrimers. All dendrimers showed bioactivity, especially second generation capped with piperazine dendrimer8, which showed inhibitory activity with IC50 of 0.9 ± 0.1 μM against Gram-positive bacteria [Methicillin-resistant Staphylococcus aureus (MRSA)] which is generally comparable to that of reference vancomycin and rifampicin. In addition, a significant increase in the anticancer activity has been observed by increasing dendrimer size. Highlights: Melamine organoiron dendrimers exhibited biological activities against bacteria and cancer targets. A significant increase in dendrimer effect with increasing dendrimer generations. The second generation capped with piperazine exhibited inhibitory activities comparable to the reference. Abstract: Three generations of a biologically active class of melamine dendrimers containing arene- cyclopentadienyliron cations were synthesized using the divergent method. These dendrimers were decorated with chloro-, hydroxyl-, or piperazine moieties. Cyclic voltammetric studies showed that dendrimers with chloro- or hydroxyl- terminal group exhibit reversible redox activity while dendrimers with piperazine moieties showed two distinct irreversible reductive waves. Organoiron dendrimers were thermally stable with the first degradation step at 200 °C associated with the decomplexation of the iron moieties. All dendrimers were evaluated against Gram-positive bacteria [Methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus warneri and vancomycin-resistant Enterococcus faecium (VRE)], and showed significant activities against bacterial strains but were found to be less active in the case of chloro- terminal group. Second generation dendrimer8 capped with piperazine exhibited inhibitory activity against Gram-positive bacteria generally comparable to that of reference vancomycin and rifampicin. Also, all dendrimers were screened against MCF-7 and HTB-26 breast cancer cell lines and dendrimer8 exhibited significant inhibitory activity against MCF-7 compared with dendrimers in lower generations.